The preparation of methyl esters and their application in epoxidation - Kocián, David (Univerzita Pardubice, 2025)
The doctoral thesis focuses on the study of preparation of methyl esters from vegetable oils and their application in epoxidation. In the first part of the thesis, methyl esters were prepared via homogeneous and heterogeneous transesterification reaction. In homogeneous transesterification (KOH), the loss of yield of methyl esters due to their transfer across the phase boundary into the glycerol phase was studied. For heterogeneous transesterification (MgAl mixed oxides), the influence of residual sodium compounds after catalyst synthesis on the (i) properties of mixed oxides, and (ii) yield of methyl esters was studied in detail. In the second part of the thesis, the application of methyl esters in epoxidation was studied. At first, various analytical methods were employed to investigate the composition of epoxidation products and to monitor the epoxidation procedure. Next, a correlation was made to help determine the iodine number using Raman spectroscopy. Then, the influence of reaction conditions (time, temperature, molar ratios of reactants, fatty acid profiles of methyl esters, intensity of stirring) on the properties of products (iodine value, epoxy index, viscosity, density) was studied. A series of equations were obtained through the use of statistical methods (QC Expert and STATISTICA softwares were used). These equations allow to predict the properties of epoxides based on the chosen reaction conditions. Afterwards, the epoxidation process of methyl esters from Camelina sativa (non-edible oil) was studied. Thermodynamic parameters of the process (H, G) were obtained through quantum chemistry calculations. Furthermore, the formation of unwanted subsequent products was explained. Eventually, novel titanium-phosphate based heterogeneous catalysts were employed for epoxidation of methyl esters from waste cooking oils/fats. These catalysts were characterized by various methods and the reaction was successfully scaled up.
Příprava metyl esterů a jejich využití v epoxidaci
Keywords: rostlinné oleje; metyl estery; transesterifikace; epoxidace; směsné oxidy; glycerol; vegetable oils; methyl esters; transesterification; epoxidation; mixed oxides; glycerol